Dictyophora indusiata and Bacillus aryabhattai improve sugarcane yield by endogenously associating with the root and regulating flavonoid metabolism - Duan, Mingzheng; Li, Xiang; Wu, Xiaojian; Long, Shengfeng; Huang, Hairong; Li, Yijie; Liu, Qi-Huai; Zhu, Guanghu; Feng, Bin; Qin, Sunqian; Li, Changning; Yang, Hai; et al. (Frontiers in Plant Science, 2024)
Endophytes play a significant role in regulating plant root development and facilitating nutrient solubilization and transportation. This association could improve plant growth. The present study has uncovered a distinct phenotype, which we refer to as "white root", arising from the intricate interactions between endophytic fungi and bacteria with the roots in a sugarcane and bamboo fungus (Dictyophora indusiata) intercropping system. We investigated the mechanisms underlying the formation of this "white root" phenotype and its impact on sugarcane yield and metabolism by metabarcoding and metabolome analysis. Initial analysis revealed that intercropping with D. indusiata increased sugarcane yield by enhancing the number of viable tillers compared with bagasse and no input control. Metabarcoding based on second-generation and third-generation sequencing indicated that D. indusiate and Bacillus aryabhattai dominates the fungal and bacterial composition in the "white root" phenotype of sugarcane root. The coexistence of D. indusiata and B. aryabhattai as endophytes induced plant growth-promoting metabolites in the sugarcane root system, such as lysoPC 18:1 and dihydrobenzofuran, probably contributing to increased sugarcane yield. Furthermore, the association also enhanced the metabolism of compounds, such as naringenin-7-Oglucoside (Prunin), naringenin-7-O-neohesperidoside (Naringin)*, hesperetin-7-O-neohesperidoside (Neohesperidin), epicatechin, and aromadendrin (Dihydrokaempferol), involved in flavonoid metabolism during the formation of the endophytic phenotype in the sugarcane root system. These observations suggest that the "white root" phenotype promotes sugarcane growth by activating flavonoid metabolism. This study reports an interesting phenomenon where D. indusiata, coordinate with the specific bacteria invade, forms a "white root" phenotype with sugarcane root. The study also provides new insights into using D. indusiata as a soil inoculant for promoting sugarcane growth and proposes a new approach for improve sugarcane cultivation.